Measuring Innovation: Trends and Characteristics (2012)
Abstract. The measurement of innovation is one of the topics that have generated more interest and controversy in the discipline of innovation management. However, due to the strong scattering studies, several approaches to this measurement have been created, which is sometimes confusing and contradictory. On the other hand, most of the literature reviews of the discipline, being mainly descriptive; do not provide a clear overview of the state of the art on the subject. Having these facts in mind, this paper is a literature review, based on the methodology of systematic analysis of the literature, allowing a clearer picture regarding the measurement of innovation, establishing the main trends and characteristics. The study identifies that, based on the literature, the innovation viewed as an organizational capability is the most important trend at the discipline.